Aproximaciones a un modelo de formación profesional - Peralta Lino, María (2012)
The present article describes the interest for the learning process model as athought expression and academic community’s projection, in the meaning andcontent of the scientific framework that provides meaning and value. Relatestheoretical positions that validate the importance of the approximate model vi sionthat guides the progressive development of knowledge in the intercultural practiceof the teaching at the University. Include referents to Santa Magdalena Sofia Baratabout the Pedagogical Model Guiding role in the formation of intellectual valuesand cognitive abilities, which confirm the impact on the culture of educationalinstitutions in contexts of complexity. Finally, mobilizes action lines derived fromthe importance of vision as a guiding force of the model in professional training,which, according to Gimeno Sacristán (1988), is the conceptual, symbolic, indirect,schematic, partial, selective representation of that reality.